The exploration of the changes in surface ozone by region and season - Firdaus Mohamad Hamzah,; Alyaa Najihah Ishak,; Nuryazmin Ahmat Zainuri,; Siti Hasliza Ahmad Rusmili,; Norshariani Abd Rahman,; Mohd Saifullah Rusiman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The growth of air pollution as a serious concern throughout the country is influenced by several causes sourcing from transportation, combustion, and industrialization. These factors reduced the air quality which harms society, animals, and plants’ well-being. Surface ozone is one of the main causes of air pollution in developing areas around the world. Analysis of surface ozone by area and season variations increased during summer were associated with meteorological parameters such as atmospheric temperature and humidity, meanwhile, the concentration of surface ozone is low during the northeast monsoon season. In addition, the concentration of surface ozone also increases when there are other environmental influences such as the release of pollutants from anthropogenic activity. Therefore, a study will be carried out to identify the variation of surface ozone concentrations by region and monsoon season in peninsular Malaysia, especially in the northern, eastern, and western zones, to identify the highest duration for daily ozone concentration (O3) and to study the relationship between the monthly and annual surface ozone concentrations with meteorological parameters. The results in this study can be used to identify air quality and address the problem of air pollution so that human health and the environment are preserved by using the method of boxplot and line graph obtained from descriptive statistics.